ANALYSIS OF THE INFLUENCE OF WORKLOAD AND SUPERVISION ON EMPLOYEE PERFORMANCE THROUGH WORK STRESS AS AN INTERVENING VARIABLE IN PRODUCTION DEPARTMENT OF PT YANMAR DIESEL INDONESIA - Rizki Hikmawan; Silverius Soeharso; Fahruddin Salim (Jurnal Saintifik (Multi Science Journal), 2023)
Work stress is often caused by work that is assigned to employees with excessive workload which can affect the quality of performance. Therefore supervision is very important to balance the two. This study aims to determine the effect of workload, work stress, and supervision on employee work performance at PT Yanmar Diesel Indonesia, and to determine work stress can mediate the effect of workload on employee performance at PT Yanmar Diesel Indonesia. This study uses a quantitative method with data collection using a Google form questionnaire. The results showed that Workload (WL) has a negative effect on employee performance (KK) with a coefficient value of -0.751. Supervision (PS) has a negative effect on employee performance (KK) with a coefficient value of -0.101. Workload (WL) has a negative effect on employee performance (KK) through work stress (SK) with a coefficient value of -0.080. Supervision (PS) has a negative effect on employee performance (KK) through work stress (SK) with a coefficient value of -0.39. Work stress (SK) has a negative effect on employee performance (KK) with a coefficient value of -0.136. Workload (WL) has a positive effect on work stress (SK) with a coefficient value of 0.587. Supervision (WL) has a positive effect on work stress (SK) with a coefficient value of 0.289.